Perfil clínico e epidemiológico das uveítes no Hospital São Geraldo/Hospital das Clínicas da Universidade Federal de Minas Gerais - Rafael de Pinho Queiroz (2017)
Introduction: Knowledge of uveitis epidemiology is important for clinical evaluation, as occurrence, etiology, outcome and severity are affected by genetic, racial, geographical, social and environmental factors. Furthermore, improvement of diagnostic methods and criteria and the emergence/reemergence of new/old entities may influence subjacent etiologies over time. Objective: To investigate clinical and epidemiological profile of uveitis subjects seen at a public university-based referral center in Southeastern Brazil over a 10-year period and to compare it to national and international published data. Methods: Longitudinal retrospective study including all patients with active uveitis consecutively seen at the Uveitis Unit of Hospital São Geraldo/HC-UFMG, between 2004 and 2013. Data analyzed consisted of age, sex, visual acuity, anatomic classification of uveitis, etiology, associated systemic diseases, HIV coinfection, surgical interventions, hospitalization and follow-up time. Results: 3683 patients were eventually included for analysis, with a mean age of 33.8 ± 15.7 years, with 1853 (50.3%) being female. Most patients were aged between 19-40 years (56.0%) and 6.7% were infected by the human immunodeficiency virus (HIV). At presentation, 1416/3620 (39.1%) patients showed BCVA ≤20/200 in at least one eye and 197/3607 (5.5%) were legally blind (BCVA ≤20/200 in the better seeing eye). Infectious uveitis was responsible for 65.5% of cases, and a specific diagnosis was possible in 72.3%, with 13.3% of cases of noninfectious uveitis being associated with an underlying systemic disease. Toxoplasmosis was the most frequent etiology (53.9%), and other infectious causes included herpes simplex/zoster (3.6%), syphilis (1.8%), HIV (1.7%), CMV (1.5%) and tuberculosis (0.7%). Among noninfectious uveitis, cases of undetermined etiology (idiopathic) prevailed, except among panuveitis, in which Vogt-Koyanagi-Harada disease(VKH) was the most frequent etiology (43.2%). Fuchs heterochromic cyclitis (FHC) was identified in 40 patients (1.1%). Gender differences were disclosed in syphilis and HIV microangiopathy, more often diagnosed in men, and in VKH, more frequent in women. Mean duration of follow-up was 11.0 ± 18.4 months (median: 2.7 months), at the end of which 1054/3627 patients (29%) had a final BCVA of ≤20/200 in at least one eye and 147/3563 (4.1%) were considered blind. Length of follow-up of cases with undetermined etiology was significantly shorter than those noninfectious cases associated with systemic diseases (9.4 ± 17.7 versus 28.5 ± 28.7 months; p<0.001). Conclusions: Uveitis affected mostly young patients, in their productive phase of life. Nearly one third evolved with significant visual impairment in at least one eye. We found an increased prevalence of infectious uveitis, particularly toxoplasmosis, herpes simplex/zoster and syphilis. The former remains the leading etiology of intraocular inflammation in our referral center. Noninfectious uveitides are still relevant, especially idiopathic anterior uveitis and Vogt-Koyanagi-Harada disease, the latter being the most common type of panuveitis. These data may subsidize strategies to prevent/improve care of individuals with uveitis.